Hero - Zhang, Yimou; Tan, Dun, 1957-; Lam, Angie, 1965-; Wada, Emi; Li, Feng, 1968-; Wang, Bin (Screenwriter); Cheng, Xiaodong, 1953-; Poon, Ellen; Li, Jet, 1963-; Leung, Tony Chiu Wai, 1962-; Zhang, Manyu; Zhang, Ziyi, 1979-; et al. (Miramax Films, 2009)
A fearless warrior rises up to defy an empire and unite a nation. With supernatural skill, and no fear, the soldier embarks on a mission of revenge against the fearsome army that has massacred his people. To achieve the justice he seeks, he must take on the empire's most ruthless assassins and reach the enemy he has sworn to defeat. The story of the First Emperor of China, who is on the brink of winning a war-torn land during the dawn of the Qin dynasty over 2,000 years ago. Three opponents are determined to kill the King, but the warrior stands in their way.